Answer:
3
Step-by-step explanation:
First we need to find the integral from 3 to 5 of g(x).
[tex]\int\limits^9_3 {g(x)} \, dx =\int\limits^5_3 {g(x)} \, dx +\int\limits^9_5 {g(x)} \, dx \\\\\int\limits^5_3 {g(x)} \, dx =\int\limits^9_3 {g(x)} \, dx -\int\limits^9_5 {g(x)} \, dx\\\\\int\limits^5_3 {g(x)} \, dx =3-4=-1[/tex]
Then the integral of interest is ...
[tex]\int\limits^5_3 {(f(x)+2g(x))} \, dx =\int\limits^5_3 {f(x)} \, dx +2\int\limits^5_3 {g(x)} \, dx =5+2(-1)\\\\\boxed{\int^5_3 {(f(x)+2g(x))} \, dx =3}[/tex]